Mushroom-Like Skin Tumours: Report of Three Cases - Wollina, Uwe (Open Access Maced J Med Sci, 2017)
Mushroom like the growth of skin tumour is a rare phenomenon although described already in 1806 by Alibert, who focused on mycosis fungicides. We identified only four case reports in PUBMED database using the terms “mushroom-like growth” and “skin tumour”. We analysed our files and identified three elderly female patients (69 to 94 years old). Histological diagnosis was melanoma, Merkel cell carcinoma and basal cell carcinoma. All tumours could be completely removed by wide excision or delayed Mohs surgery. No metastatic spread was noted.